Biocomposites and natural fibers for oil-water separation: a review on materials, modifications, and performance - Santos de Andrade Segantine, Arieli; Sérgio da Silva Porto, Paulo (Latin American Journal of Energy Research, 2025)
The continuous expansion of industrialization, energy demand, and economic development has been directly correlated with the increasing incidence of oil spills and the discharge of oily effluents, posing an environmental and ecological risk of global magnitude that threatens human health and the sustainability of aquatic ecosystems. The development of sustainable sorbent materials for the treatment of oily effluents is primarily based on the valorization of agricultural biomass residues, whose structure is mainly composed of natural fibers such as cellulose, hemicellulose, and lignin. This study conducts a systematic review of the recent literature on natural fiber-reinforced polymer composites applied to the treatment of oily effluents. The analysis focuses on modification strategies and evaluates the materials’ performance in terms of sorption capacity, selectivity, reusability, and stability.